In vitro regulation of IL-6 and TGF-ß by mesenchymal stem cells in systemic lupus erythematosus patients - Dewi Masyithah Darlan; Delfitri Munir; Nelva Karmila Jusuf; Agung Putra; Riyadh Ikhsan; Iffan Alif (Medicinski glasnik, 2020)
Aim: To analyse the ability of mesenchymal stem cells (MSCs) to regulate interleukin 6 (IL-6) and transforming growth factor (TGF-?) expression in vitro under co-culture conditions in human systemic lupus erythematosus (SLE). Method: This study used a post-test group design that used peripheral blood mononuclear cells (PBMCs) from SLE patients at Kariadi Hospital, Semarang, Indonesia, and MSCs from a human umbilical cord. The cells were divided into two groups. The control group of PBMCs was treated with a standard medium, and the treatment group was co-cultured with the MSCs at a 1:40 ratio. Following 24 h incubation, the levels of IL-6 and TGF-? released in the culture medium were measured using a specific ELISA assay. Results: This study showed a significant decrease in IL-6 level (p< 0.05) and a significant increase in TGF-? level (p<0.001) following 24 h of co-culture incubation of human SLE PBMCs cells and MSCs. Conclusion: The PBMCs-to-MSCs ratio of 1:40 can regulate the IL-6 and TGF-? levels in human SLE PBMCs.
Keywords: autoimmune disease; cytokine dysregulation; immunoregulation; inflammatory disorder